(untitled) (Research, Society and Development, 2024)
The COVID-19 pandemic, caused by the SARS-CoV-2 coronavirus, is a serious health problem on a global scale. The purpose of the research was to analyze the epidemiological profile of cases and deaths from Severe Acute Respiratory Syndrome (SARS), with a focus on COVID-19, in Minas Gerais during the period from 2021 to 2023. A descriptive and quantitative study was carried out, using data secondary, with the calculation of absolute and relative frequencies, measures of central tendency and dispersion, incidence and lethality rates. In 2021, 65,535 cases of SARS were reported in the SIVEP_Gripe system, of which 42,926 (65.5%) were confirmed as COVID-19, resulting in 13,317 deaths. In 2022, 61,712 cases of SARS were recorded, of which 28,108 (45.4%) were confirmed as COVID-19, with 7,487 deaths. In 2023, there were 63,184 cases of SARS, of which 11,909 (18.9%) were confirmed as COVID-19, resulting in deaths. The incidence was 209/100,000, 137/100,000 and 58/100,000, with fatality rates of 31.0%, 28.0% and 18.6% for the years 2021, 2022 and 2023, respectively. The prevalence was higher in males in 2021 and 2023 and in females in 2022, with average ages of 58, 70 and 68 for cases and 67, 77 and 76 for deaths in the years 2021, 2022 and 2023. There was a predominance of white race/color, present in 38.6% to 51.0% of cases and 44.3% to 52.6% of deaths in the same period, in addition to the presence of comorbidities in 67.6% and 86.6% of cases and deaths, respectively. The hospitalization rate was 98.0% and 95.2% for cases and deaths, with 64.3% of patients not requiring ICU and 58.3% of deaths remaining in intensive care. Additionally, 45.6% and 42.4% of cases and deaths received non-invasive ventilatory support, with 78.8% and 87.3% vaccinated against COVID-19. The importance of identifying priority groups, understanding the behavior of the virus in the state and implementing public policies aimed at this specific population is highlighted.